2009
DOI: 10.1002/bsl.878
|View full text |Cite
|
Sign up to set email alerts
|

Stress experiences of family members of registered sex offenders

Abstract: The collateral consequences of sex offender registration and notification (SORN) have been well established, although little evidence has supported the efficacy of SORN. Based on the belief that family members provide some of the most consistent, important, and intense forms of support for criminal offenders in general and registered sex offenders (RSOs) more specifically, the experiences of sanctions, losses, and stresses of these individuals is examined. Using survey responses from 584 individuals known to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 30 publications
6
147
0
1
Order By: Relevance
“…Although these laws have helped to increase the visibility of this issue and hopefully increase victim access services and justice, research also seems to indicate some unintentional consequences. These consequences include family members' struggles with the shame and stigma of public notification, families being less likely to seek help fearing the possible consequences they may face, and families possibly being less likely to see sexual abuse when most offenders are portrayed as monsters by the media (McCartan et al, 2015;McLean & Maxwell, 2015;Tabachnick & Klein, 2010;Pittman, 2013;Tewksbury & Levenson, 2009). …”
Section: The Need For a Paradigm Shiftmentioning
confidence: 99%
“…Although these laws have helped to increase the visibility of this issue and hopefully increase victim access services and justice, research also seems to indicate some unintentional consequences. These consequences include family members' struggles with the shame and stigma of public notification, families being less likely to seek help fearing the possible consequences they may face, and families possibly being less likely to see sexual abuse when most offenders are portrayed as monsters by the media (McCartan et al, 2015;McLean & Maxwell, 2015;Tabachnick & Klein, 2010;Pittman, 2013;Tewksbury & Levenson, 2009). …”
Section: The Need For a Paradigm Shiftmentioning
confidence: 99%
“…Such adverse consequences are again seen in Tewksbury's (2004) study, where he examined the experiences and perceptions of 40 female sex offenders in Kentucky. From the experiences of these women, the researcher found that "far-reaching implications" existed for "individuals listed on registries" (p. 32).…”
Section: Negative Experiences With Sex Offender Policiesmentioning
confidence: 99%
“…Respondents have an average of more than eight years of experience as a prison warden, and their political I This less-than-desirable response rate is acknowledged. However, previous studies concerning perceptions of sex offenders and sex offender policies are also limited by lower response rates (Kernsmith, et aI., 2009;Levenson & Cotter, 2005;Tewksbury, 2004Tewksbury, , 2005Tewksbury & Humkey, 2010; views are self-characterized as more conservative than liberal. The respondents represent each of the 19 randomly selected jurisdictions in the United States.…”
Section: Samplementioning
confidence: 99%
“…Even though males make up the majority of sex offenders who offend against children, female adults also offend (Giguere & Bumby, 2007;Nathan & Ward, 2002;Tewksbury, 2004;Vandiver & Walker, 2002). As such, typologies of female sex offenders have been developed to better understand this phenomenon.…”
Section: Adult Sexual Victimizationmentioning
confidence: 99%